Estimated prevalence of human toxocariosis in Lima Region - Blanco, Yrma Espinoza (2016)
Objective. To estimate frequency of toxocariosis in Lima Region. Methods. During 2013, a non-randomized serological survey was performed by Elisa technique in four Lima Region provinces’ (Cajatambo, Canta, Huaral and Yauyos) inhabitants. Sera samples were obtained by DIRESA Lima and Regional Reference Laboratory of Public Health workers and processed at Tropical Medicine Institute “Daniel A. Carrion” of Universidad Nacional Mayor de San Marcos, Lima, Peru. Results. From 442 sera samples obtained 142 (32.1%) were positive to Toxocara; 54% of participants were female, 31% were between 31-59 years, 45% had a dog or cat at home. There were no significant differences between serology and ages or sex or in having dog or cats. Conclusions. Toxocariosis is frequent in Lima Region inhabitants. It is necessary to perform representative studies to determine prevalence of this infection.